1058 Racial/Ethnic Sleep Disparities Among College Students Are Different in Majority-White vs Majority-Minority Institutions. (27th April 2018) - Okuagu, A; Athey, A; Prichard, R; Williams, N; Jean-Louis, G; Killgore, W; Gehrels, J; Alfonso-Miller, P; Grandner, M
Abstract: Introduction: Racial/ethnic sleep disparities are well-documented and may be related to discrimination. The present study examined sleep among minority college/university students, and whether these sleep disparities exist differently at institutions that are predominantly White versus non-predominantly White. Methods: Data from the 2011–2014 National College Health Assessment conducted by the American College Health Association was used (N=112, 849 students). Race/ethnicity was categorized as Non-Hispanic White, Black/African-American, Hispanic/Latino, Asian, Native American, Multiracial, or Other. Schools with a majority of respondents who were not Non-Hispanic White were classified as majority minority schools. Sleep was assessed as whether sleep difficulties had been "particularly traumatic or difficult to handle in the past 12 months" and as number of nights per week they got "enough sleep to feel refreshed, " categorized as 0–1, 2–3, 4–5, or 6–7 (reference). Covariates included age, sex, year in school, and survey year. Logistic regressions examined prevalence of sleep difficulty or insufficient sleep by race/ethnicity, stratified by school type. Results: A race/ethnicity by school type interaction was significant for both sleep variables (p<0.0001). In majority Non-Hispanic White schools, sleep difficulty was more common among Hispanics/Latinos (OR=1.14, 95%CI[1.09, 1.20], p<0.0001), Native Americans (OR=1.39, 95%CI[1.26, 1.54], p<0.0001), Multiracials (OR=1.52, 95%CI[1.44, 1.61], p<0.0001), and Others (OR=1.18, 95%CI[1.07, 1.30], p=0.001) and less sleep difficulty was seen among Asians (OR=0.89, 95%CI[0.85, 0.94], p<0.0001). In majority minority schools, though, Multiracials demonstrated greater sleep difficulty (OR=1.37, 95%CI[1.08, 1.74, p=0.010) and less sleep difficulty was seen for Blacks/African-Americans (OR=0.76, 95%CI[0.60, 0.96], p=0.021) and Asians (OR=0.72, 95%CI[0.56, 0.92], p=0.009). For insufficient sleep, prevalence of only 0–1 nights of sufficient sleep in majority Non-Hispanic White schools was higher among Blacks/African-Americans (RRR=1.22, 95%CI[1.10, 1.34], p<0.0001), Hispanics/Latinos (RRR=1.32, 95%CI[1.22, 1.43], p<0.0001), Asians (RRR=1.12, 95%CI[1.04, 1.21], p=0.004), Native Americans (RRR=1.41, 95%CI[1.17, 1.68], p<0.0001), and Multiracials (RRR=1.48, 95%CI[1.34, 1.63], p<0.0001). In majority minority schools, though, increased prevalence of 0–1 nights of sufficient sleep was seen only for Hispanics/Latinos (RRR=1.60, 95%CI[1.27, 2.01], p<0.0001). Conclusion: More sleep difficulty and insufficient sleep was reported at majority-white institutions, though no association was observed between school type and sleep sufficiency in Hispanics/Latinos. Other social-environmental influences may be involved. Support (If Any):